Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Mewarnai Pada Anak UPT SD Negeri 060841, Medan Petisah - Puput Kritine Buulolo; Tuti Atika (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Teaching Campus is a learning channel that provides opportunities for students to study off-campus for one semester in order to practice their ability to solve complex problems by becoming partners with teachers to innovate in learning, develop strategies and learning models that are creative, innovative and fun. This program was formed by the Ministry of Education and Culture of the Republic of Indonesia which aims to improve the existing education system in Indonesia. Improvement of the education system also starts from elementary schools to junior high schools. The program that will be carried out at UPT SDN 060841 is an activity to improve fine motor skills through coloring activities. This activity aims to improve quality and to develop movement skills of both hands, as a tool to develop coordination of hand speed with eye movements. As a tool to train the mastery of emotions. The basic concept of this activity is coloring like living things, the environment etc. Children can also express feelings and train children to learn to concentrate and imagine. Improving Fine Motoric Skills Through Coloring Activities. This activity aims to improve quality and to develop movement skills of both hands, as a tool to develop coordination of hand speed with eye movements. As a tool to train the mastery of emotions. The basic concept of this activity is coloring like living things, the environment etc. Children can also express feelings and train children to learn to concentrate and imagine.